Echo Across the Ocean- Selected Prose Of Hamzah Hussin and The House Of Earth Trilogy By Pearl S. Buck: (Gema Merentas Lautan: Prosa Terpilih Hamzah Hussin dan Trilogi The House of Earth oleh Pearl S. Buck) (Malay Literature, 2019)
This paper focuses on the issue of external contacts in early modern Malay literature in the 20th century. It applies historical and comparative methods of research to three renowned novels by the Malay author, Hamzah Hussin, written between 1951 and 1956. This paper aims to trace their possible connection with the famed The House of Earth trilogy (1931-1935) by the American Nobel Prize Laureate, Pearl S. Buck. The results of analysis demonstrate notable correspondences between the respective novels of Hamzah Hussin and Pearl S. Buck on the level of issues raised and storyline. Both sets of novels also share the same central image of house/home, which provides the core development of plot. Additionally, the women characters are found to share commonalities in both sets of novels. It is hoped that this paper prompts future studies on the Occidental influences in Malay authors and literature.Keywords: Malay literature, American prose, novel, Hamzah Hussin, Pearl S. Buck, literary contacts, Occidental influence